Predictive Validity of Operationalized Criteria for the Assessment of Criminal Responsibility of Sexual Offenders With Paraphilic Disorders—A Randomized Control Trial With Mental Health and Legal Professionals - Dobbrunz, Sascha; Daubmann, Anne; Müller, Jürgen Leo; Briken, Peer (Frontiers in Psychology, 2020)
The prevention of sexual violence is a major goal of sexual health. In cases of accused sexual offenders, the assessment of diminished criminal responsibility of the accused is one of the most important procedures undertaken by experts in the German legal system. This assessment follows a two-stage method assessing firstly the severity of a paraphilic disorder and then secondly criteria for or against diminished capacity. The present study examines the predictive validity of two different sets of criteria for the assessment of criminal responsibility in the context of paraphilic disorders combined with sexual offending. Two exemplary case vignettes of two suspected sexual offenders were developed to assess the criteria. For each participant, one of the two exemplary case vignettes were randomly presented. The presentation of the two different sets of criteria was also randomized, so that each participant was assigned only one of the two criteria sets to rate one of the presented cases. N=349 participants from different professional backgrounds (mental health and legal professionals) completed their assessments and were included in the data analysis. The data was evaluated using logistic regression. Results show that the more recently published criteria set (Briken and Müller, 2014) predicts both the severity of the disorder as well as the diminished capacity twice as good as the older criteria set of Boetticher et al. (2005) currently used for forensic court reports. In preliminary conclusion the new criteria of Briken and Müller (2014) form an empirically based assessment of criminal responsibility. However, the proposed criteria cannot replace an extensive exploration of the accused person and a careful file analysis. Validity and reliability of the results are also limited due to the methodical choice of a vignette study.